Gender-specific Call of Duty : A Note on the Neglect of Conscription in Gender Equality Indices - Heikkilä, Jussi; Laukkanen, Ina (Defence and Peace Economics, 2022)
We document that existing gender equality indices do not account for gender-specific mandatory peace-time conscription (compulsory military service). This suggests that gender-specific conscription is not considered to be an important gender issue. If an indicator measuring the gender equality of mandatory conscription was to be included in gender equality indices with appropriate weight, then the relative rankings of countries in terms of measured gender equality could be affected. In the context of the Nordic countries, this would mean that Finland and Denmark – the countries with mandatory conscription for men only – would have worse scores with respect to gender equality compared to Sweden and Norway, countries with conscription for both men and women – and Iceland, which has no mandatory conscription, regardless of gender. peerReviewed